Finance companies in Mexico: Unexpected victims of the global liquidity crunch - Berrospide, Jose M.; Herrerias, Renata (Journal of Financial Stability, 2015)
We study the connection between the global liquidity crisis and the severe credit crunch experienced by finance companies (SOFOLES) in Mexico using firm-level data between 2001 and 2011. Our results provide supporting evidence that, as a result of the liquidity shock, SOFOLES faced severely restricted access to their main funding sources (commercial bank loans, loans from other organizations, and public debt markets). After controlling for the potential endogeneity of their funding, we find that the liquidity shock explains 64 percent of SOFOLES’ credit contraction during the recent financial crisis (2008–2009). We use our estimates to disentangle supply from demand factors as determinants of the credit contraction. After controlling for the large decline in loan demand during the financial crisis, our findings suggest that supply factors (such as nonperforming loans and lower liquidity buffers) also played a significant role. Finally, we find that financial deregulation implemented in 2006 may have amplified the effects of the global liquidity shock.